Investigating the Effect of Mergers and Acquisitions on Firm’s Operating Performance - JIANG, ZHAOYANG (2010)
Previous research results about the effect of Mergers and Acquisitions on the performance of firms are ambiguous. Using firms matched on the basis of size and industry as the benchmark and several operating performance measures, the evidence from this study imply that Mergers and Acquisitions completed in the US with minimum deal value $500 million over the period 2000 to 2005 result in no significant improvements in operating performance. Further, there is some evidence that the type of the Mergers and Acquisitions and the method of payment have no impact on the postmerger performance.